The The Merbabu Park in Malang City with a Family Park Approach as an Effort to Enhance Visitor Comfort: Taman Merbabu Kota Malang Dengan Pendekatan Family Park Sebagai Upaya Meningkatkan Kenyamanan Pengunjung - Anjenita Kurniati, Wulan (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Because of the current rapid urban growth in the city of Malang, infrastructure projects like Merbabu Park are necessary. Unfortunately, the park's design and resource utilization are not optimal, diminishing the overall visitor experience. In response to these challenges, the local government has initiated plans to visually enhance the park by installing CCTV systems and improving facilities, prioritizing increased comfort and security. The proposed solution employs a Family Park approach and narrative design, focusing on layout improvements without expanding its physical footprint. To deliver a unique and appealing solution, it is crucial to leverage cutting-edge technology, creative approaches, and contemporary artistic trends. To enhance visitor comfort and security, the renovation of Merbabu Family Park in Malang adopts a Family Park-based design. Upgraded interactive components, CCTV installations, and optimized layouts are among the modifications. The design incorporates elements of the 5 family aspects in futsal areas, outdoor gyms, and relaxation spaces alongside various interactive components. The intended ambiance of optimism, safety, and refreshment is achieved through the use of organic forms, circular motifs, and shading. By implementing these ideas, Merbabu Family Park aims to become a family-friendly and attractive recreational area that ultimately enhances the city's tourism appeal and promotes community happiness and engagement.